Nonexistence of coexisting steady‐state solutions of Dirichlet problem for a cross‐diffusion model. (22nd October 2018) - Zhu, Ningning; Tang, De
Abstract : We study a special case of Shigesada–Kawasaki–Teramoto (SKT) model for two competing species with the Dirichlet boundary conditions. In our case, one of the species is not influenced by self‐diffusion or cross‐diffusion. We specify the explicit range of parameters by contradiction such that there are no coexisting steady‐state solutions to the model.